A new species of Sakuraeolis from Mozambique, described using 3D reconstruction of anatomy and phylogenetic analysis. (18th May 2021) - Ellis-Diamond, Dawn C; Picton, Bernard E; Tibiriçá, Yara; Sigwart, Julia D
ABSTRACT: Here we describe a new species of shallow-subtidal nudibranch from south-eastern Africa. The strikingly vivid orange sea slug with white markings belongs to the long-disputed family Facelinidae, and has been photographed and recorded in the region by divers for some time. Tomographic modelling was applied to produce a 3D anatomical reconstruction of the reproductive and digestive organs from serial sections. A molecular phylogeny using multiple markers (cytochrome c oxidase subunit I, 16S rRNA and histone H3) recovered three distinct clades within the paraphyletic Facelinidae, in agreement with other recent studies. This topology supported a genus-level clade, including the type species of Sakuraeolis Baba, 1965, S. enosimensis Baba, 1930, the new species described herein, S. arcana n. sp., and an undescribed sibling species that shares morphological resemblance to S. arcana n. sp. Facelina quatrefagesi Vayssière, 1888 is also recognized as Caloria quatrefagesi n. comb. on the basis of molecular and morphology affinity. Field observations provided insight into phenology, with a population decline noted in August. Although the new species does not have the penial structure previously considered diagnostic for Sakuraeolis, the decision was made on the balance of evidence for phylogenetic affinity to amend the diagnosis of the genus to accommodate S. arcana n. sp.